Schizophrenia literacy: the effects of an educational intervention on populations with and without prior health education. (4th May 2019) - Thorsteinsson, Einar B.; Bhullar, Navjot; Williams, Elizabeth; Loi, Natasha M.
Abstract: Background: Mental health literacy is an important predictor of appropriate help-seeking behaviour. Aims: This study investigated (a) the effects of an educational intervention on schizophrenia mental health literacy, beliefs about causes, discrimination, treatment, and attitudes that promote recognition, and (b) whether schizophrenia literacy would be higher in people with prior education in a health-related area than people without such education. Method: A randomised control design tested the effects of an educational intervention on schizophrenia literacy relative to a control group. Participants ( N  = 260; mean age = 31.18 years, SD  = 11.43, female = 78.8%) answered a mental health literacy questionnaire, based on a vignette of a person with schizophrenia, before and after watching either an educational video on schizophrenia or a control video. Results: The intervention significantly increased schizophrenia identification and literacy, reduced personal stigma, and increased perceived discrimination in society. The health background group reported significantly greater schizophrenia identification than the no health background group. Participants thought help should be sought from health care professionals and through psychotherapy, close friends and physical activity. Conclusions: Targeted education can significantly improve the ability to identify schizophrenia which may have positive implications for reducing the time individuals take to seek help.